Acute and regular exercise distinctly modulate serum, plasma and skeletal muscle BDNF in the elderly. (December 2019) - Máderová, Denisa; Krumpolec, Patrik; Slobodová, Lucia; Schön, Martin; Tirpáková, Veronika; Kovaničová, Zuzana; Klepochová, Radka; Vajda, Matej; Šutovský, Stanislav; Cvečka, Ján; Valkovič, Ladislav; Turčáni, Peter; et al.
Abstract: Brain-derived neurotrophic factor (BDNF) participates in orchestrating the adaptive response to exercise. However, the importance of transient changes in circulating BDNF for eliciting whole-body and skeletal muscle exercise benefits in humans remains relatively unexplored. Here, we investigated effects of acute aerobic exercise and 3-month aerobic-strength training on serum, plasma and skeletal muscle BDNF in twenty-two sedentary older individuals (69.0 ± 8.0 yrs., 9 M/13F). BDNF response to acute exercise was additionally evaluated in young trained individuals (25.1 ± 2.1 yrs., 3 M/5F). Acute aerobic exercise transiently increased serum BDNF in sedentary (16%, p = .007) but not in trained elderly or young individuals. Resting serum or plasma BDNF was not regulated by exercise training in the elderly. However, subtle training-related changes of serum BDNF positively correlated with improvements in walking speed ( R = 0.59, p = .005), muscle mass ( R = 0.43, p = .04) and cognitive performance ( R = 0.41, p = .05) and negatively with changes in body fat (R = -0.43, p = .04) and triglyceridemia (R = -0.53, p = .01). Individuals who increased muscle BDNF protein in response to 3-month training (responders) displayed stronger acute exercise-induced increase in serum BDNF than non-responders ( p = .006). In addition, muscle BDNF protein content positively correlated with type II-to-type I muscle fiber ratio ( R = 0.587, p = .008) and with the rate of post-exercise muscle ATP re-synthesis ( R = 0.703, p = .005). Contrary to serum, acute aerobic exercise resulted in a decline of plasma BDNF 1 h post-exercise in both elderly-trained (−34%, p = .002) and young-trained individuals (−48%, p = .034). Acute circulating BDNF regulation by exercise was dependent on the level of physical fitness and correlated with training-induced improvements in metabolic and cognitive functions. Our observations provide an indirect evidence that distinct exercise-induced changes in serum and plasma BDNF as well as training-related increase in muscle BDNF protein, paralleled by improvements in muscle and whole-body clinical phenotypes, are involved in the coordinated adaptive response to exercise in humans. Highlights: Acute exercise increases serum BDNF in the sedentary elderly and the response is blunted by aerobic-strength training. Plasma BDNF is reduced 1 h post-exercise in exercise-trained elderly & young individuals, but not in sedentary seniors. Training effect on serum BDNF is linked to improved walking speed, muscle mass & cognition and to lower body fat. Training-induced increase in muscle BDNF protein parallel adaptive changes in muscle structure, function & metabolism.